Examining the investment decision-making process of retail investors based on Robinhood user data - Walz-Nickol, Philipp Marvin (2023)
This paper analyzes both the risk behavior and investment decision-making process of users of the retail brokerage platform Robinhood Markets, Inc., based on publicly available holdings data. I find that Robinhood users engage disproportionately in unusual stocks. Applying a mul tivariate OLS regression, one can see that they tend to overweight mediocrely reputable infor mation sources. Analyzing their consensus performance versus comparative portfolios, one can observe that the users cannot outperform less volatile benchmarks. Further, they take on unnec essary risk due to a lack of diversification and overweighting of particular securities, indicating that modern retail investors behave riskier than traditional individual investors.